Analysis Of The Quality Of Service Of SPHP Rice Distribution In The Distribution Network (TPK And RPK) In Perum Bulog Regional Office Yogyakarta - Rizqika Farhan; Nursya’bani Purnama (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the quality of rice distribution services in the Food Supply and Price Stabilization Program (SPHP) carried out by Perum BULOG Kanwil Yogyakarta through the Rumah Pangan Kita (RPK) and Toko Pangan Kita (TPK) distribution networks. This study uses a quantitative approach with data collection techniques through closed questionnaires distributed to 100 distributors as respondents. The analysis was carried out using the SERVQUAL model which includes five dimensions of service quality: reliability, responsiveness, assurance, empathy, and tangibles. The results showed that all dimensions of service quality were in the "good" category with an overall average score of 4.14, which reflects the level of distributor satisfaction with BULOG's services. However, the assurance dimension obtained the lowest relative score, indicating the need for improvements in the aspects of trust and competence of officers in maintaining rice quality. The implications of this study are the importance of improving officer training, strengthening communication with distributors, and handling complaints more responsively in order to increase distribution effectiveness and strengthen partner trust in supporting national food security.